Implementation of a Memcapacitor Emulator with Off-the-Shelf Devices - Sah, M. P.; Yang, C.; Budhathoki, R. K.; Kim, H.; Yoo, H. J. (Elektronika ir Elektrotechnika, 2013)
We implemented a memcapacitor emulator with off-the-shelf electronic devices. The memcapacitor is an element whose capacitance can be altered with external current or voltage. The implementation of the emulator is very important since commercial versions are not yet available. The proposed memcapacitor emulator has a simple dedicated memcapacitor architecture that does not require a mutator. It is the first memcapacitor emulator implemented with commercially available devices. The operation as a memcapacitor has been proven via both breadboard experiments and PSPICE simulations. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.2673